The Influence of Entrepreneurship Education in Fostering Students' Entrepreneurial Intention: A Literature Study - Pratiwi, Kunti Endah; Prihastya Raehana.A; Ludi Wishnu Wardana; F. Danardana Murwani; Andy Prasetyowati (Profesional Muda Cendekia Publishing, 2024)
This study aims to find the effect of entrepreneurship education in fostering entrepreneurial intentions in students. The method used in summarising the results of the journal review is a systematic literature review (SLR). The population of this research is college students. The results showed that: 1) entrepreneurship education in fostering entrepreneurial intentions in students does not affect directly but through mediation of other factors. 2) the duration of entrepreneurship education has a great influence on fostering entrepreneurial intentions in students. 3) entrepreneurship education should be delivered in adolescence by using learning techniques that follow the personal character of students. And also 4) entrepreneurship education is also able to influence the level of business activity or business performance of an entrepreneur.